A 60 ksi grade sulfur-resistant oil casing and method of making the same

CN123005233APending Publication Date: 2026-10-30YANAN JIASHENG PETROLEUM MACHINERY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611294628.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]基于上述现有技术的不足,本发明的目的在于提供一种60ksi钢级抗硫油套管及其制备方法,旨在解决现有油套管无法兼顾较高的强度、良好的韧性以及耐H2S应力腐蚀和氢致开裂性能的问题

Benefits of technology

[0017]有益效果:本发明提供的60ksi钢级抗硫油套管的屈服强度为414~552MPa,抗拉强度≥552MPa,伸长率为31%~35%,0℃横向夏比V型缺口冲击功≥80J,金相组织为针状铁素体+粒状贝氏体,晶粒度为10.0~11.5级,按照NACE TM 0177 A法在A溶液中加载95%规定最低屈服强度(SMYS)应力水平(393MPa)720小时试验不产生裂纹或断裂,按照NACE TM0284在饱和H2S溶液中试验96小时未出现裂纹,具有良好的抗硫性能(抗H2S应力腐蚀和氢致开裂性能)。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a 60ksi-grade sulfur-resistant oil casing and a preparation method thereof, and relates to the technical field of oil casing manufacturing. The 60ksi-grade sulfur-resistant oil casing mainly comprises the following chemical components in percentage by mass: C 0.10%-0.15%, Si 0.17%-0.37%, Mn 1.05%-1.28%, P≤0.012%, S≤0.003%, Al 0.010%-0.018%, Ca 0.007%-0.015%, N≤0.005%, O≤0.002%, H≤0.00015%, Cr 0.15%-0.25%, V 0.035%-0.060%, RE 0.001%-0.005%, the yield strength of the 60ksi-grade sulfur-resistant oil casing is 414-552 MPa, the tensile strength is greater than or equal to 552 MPa, the 0 DEG C transverse Charpy V-type notch impact energy is greater than or equal to 80 J, and the 60ksi-grade sulfur-resistant oil casing has good sulfur resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of oil casing manufacturing technology, and in particular to a 60ksi steel grade anti-sulfur oil casing and its preparation method. Background Technology

[0002] With the continuous development of sulfur-containing oil and gas fields, the demand for casing and tubing resistant to H2S stress corrosion and hydrogen-induced cracking is increasing. H2S stress corrosion and hydrogen-induced cracking are among the main forms of casing and tubing failure during the exploitation of sulfur-containing oil and gas fields, seriously threatening the production safety of oil and gas wells. Studies have shown that through reasonable alloy design and processing technology, it is possible to obtain casing and tubing steels and their products that possess both high strength and high sulfur resistance.

[0003] Traditional anti-sulfur oil casings are mostly designed using Cr-Mo alloys, achieving a tempered sorbite microstructure through quenching and tempering heat treatment to meet the anti-sulfur performance requirements of the NACE standard. However, traditional processes suffer from high alloy costs, long production processes, and high energy consumption. In recent years, breakthroughs in online microstructure control technology for controlled rolling and cooling in the field of hot-rolled seamless steel pipes have provided a new approach for low-cost, high-efficiency production of high-performance anti-sulfur oil casings. By controlling the microstructure during rolling and the cooling path after rolling, combined with online self-tempering, the combined effects of fine grain strengthening, precipitation strengthening, and phase transformation strengthening can be fully utilized, further simplifying the production process while ensuring anti-sulfur performance.

[0004] Studies have shown that the combined use of Cr and Mo elements is an important means to improve sulfur resistance. Appropriate addition of Cr and Mo can improve the hardenability of steel, refine carbides, and enhance tempering stability. However, for 60ksi grade oil casing, both Cr-Mo alloy design and quenching and tempering heat treatment significantly increase costs. Currently, for 55ksi-80ksi grade non-quenched and tempered ordinary oil casing, low to medium carbon (0.25%–0.45%), higher Mn (1.4%–1.8%), and selective addition of elements such as Cr, Si, B, N, Nb, V, and Ti are commonly used. While this material meets strength requirements, its toughness is insufficient, and its resistance to H2S stress corrosion and hydrogen-induced cracking is inadequate.

[0005] Therefore, existing technologies still need to be improved and developed. Summary of the Invention

[0006] Based on the shortcomings of the prior art, the purpose of this invention is to provide a 60ksi grade anti-sulfur oil casing and its preparation method, aiming to solve the problem that existing oil casings cannot simultaneously achieve high strength, good toughness, and resistance to H2S stress corrosion and hydrogen-induced cracking.

[0007] The technical solution of the present invention is as follows: In a first aspect, the present invention provides a 60ksi grade anti-sulfur oil casing, wherein the 60ksi grade anti-sulfur oil casing comprises the following chemical components in weight percentages: C 0.10%~0.15%, Si 0.17%~0.37%, Mn 1.05%~1.28%, P≤0.012%, S≤0.003%, Al0.010%~0.018%, Ca 0.007%~0.015%, N≤0.005%, O≤0.002%, H≤0.00015%, Cr 0.15%~0.25%, V 0.035%~0.060%, RE 0.001%~0.005%, balance Fe and unavoidable impurities; The metallographic structure of the 60ksi grade anti-sulfur oil casing consists of acicular ferrite and granular bainite with a grain size of 10.0–11.5. Its yield strength is 414–552 MPa, tensile strength ≥552 MPa, elongation 31%–35%, and transverse Charpy V-notch impact energy ≥80 J at 0℃. It can withstand 95% loading at the specified minimum yield strength in solution A for 720 hours according to NACE™ 0177 A method without cracking or fracture. It also shows no cracking after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

[0008] A second aspect of the present invention provides a 60ksi grade anti-sulfur oil casing, wherein the 60ksi grade anti-sulfur oil casing comprises the following chemical components in weight percentages: C 0.10%~0.15%, Si 0.17%~0.37%, Mn 1.05%~1.28%, P 0.008%~0.012%, S 0.0015%~0.0020%, Al 0.010%~0.018%, Ca 0.007%~0.015%, N 0.0035~0.0045%, O 0.0015%~0.0019%, H 0.00010%~0.00014%, Cr 0.15%~0.25%, V 0.035%~0.060%, RE 0.001%~0.005%, balance Fe and unavoidable impurities; The metallographic structure of the 60ksi grade oil casing is acicular ferrite and granular bainite, with a grain size of 10.0–11.5. The yield strength is 470–535 MPa, the tensile strength is 595–665 MPa, the elongation is 31%–35%, and the transverse Charpy V-notch impact energy at 0℃ is 85–112 J. It can withstand 95% of the specified minimum yield strength in solution A for 720 hours according to NACE™ 0177 A method without cracking or fracture. It also shows no cracking after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

[0009] A third aspect of the present invention provides a 60ksi grade anti-sulfur oil casing, wherein the 60ksi grade anti-sulfur oil casing comprises the following chemical components in weight percentages: C 0.10%~0.13%, Si 0.25%~0.37%, Mn 1.15%~1.28%, P 0.008%~0.012%, S 0.0015~0.0020%, Al 0.010%~0.015%, Ca 0.010%~0.015%, N 0.0035%~0.0042%, O 0.0015%~0.0019%, H 0.00010%~0.00014%, Cr 0.18%~0.25%, V 0.045%~0.060%, RE 0.0010%~0.0035%, balance Fe and unavoidable impurities; The metallographic structure of the 60ksi grade oil casing is acicular ferrite and granular bainite, with a grain size of 10.5–11.5. The yield strength is 490–535 MPa, the tensile strength is 620–665 MPa, the elongation is 31%–34%, and the transverse Charpy V-notch impact energy at 0℃ is 96–112 J. It can withstand 95% of the specified minimum yield strength in solution A for 720 hours according to NACE™ 0177 A method without cracking or fracture. It also shows no cracking after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

[0010] A fourth aspect of the present invention provides a 60ksi grade anti-sulfur oil casing, wherein the 60ksi grade anti-sulfur oil casing comprises the following chemical components in weight percentages: C 0.10%~0.13%, Si 0.28%~0.37%, Mn 1.18%~1.28%, P 0.009%~0.012%, S 0.002%, Al 0.010%~0.014%, Ca 0.011%~0.015%, N 0.0038%~0.0042%, O 0.0015%~0.0019%, H 0.00010%~0.00014%, Cr 0.18%~0.25%, V 0.048%~0.060%, RE 0.0010%~0.0035%, balance Fe and unavoidable impurities; The metallographic structure of the 60ksi grade oil casing is acicular ferrite and granular bainite, with a grain size of 10.5-11.5. The yield strength is 510-535 MPa, the tensile strength is 635-665 MPa, the elongation is 31%-33%, and the transverse Charpy V-notch impact energy at 0℃ is 96-112 J. It can withstand 95% of the specified minimum yield strength in solution A for 720 hours according to NACE™ 0177 A method without cracking or fracture. It also shows no cracking after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

[0011] A fifth aspect of the present invention provides a 60ksi grade anti-sulfur oil casing, wherein the 60ksi grade anti-sulfur oil casing comprises the following chemical components in weight percentages: C 0.11%~0.13%, Si 0.28%~0.32%, Mn 1.18%~1.22%, P 0.009%~0.010%, S 0.002%, Al 0.012%~0.014%, Ca 0.011%~0.012%, N 0.0038%~0.0040%, O 0.0015%~0.0019%, H 0.00010%~0.00014%, Cr 0.23%~0.25%, V 0.048%~0.055%, RE 0.0030%~0.0035%, balance Fe and unavoidable impurities; The metallographic structure of the 60ksi grade oil casing is acicular ferrite and granular bainite, with a grain size of 10.5-11.0. The yield strength is 525-535 MPa, the tensile strength is 650-665 MPa, the elongation is 31%-32%, and the transverse Charpy V-notch impact energy at 0℃ is 96-100 J. It can withstand 95% of the specified minimum yield strength in solution A for 720 hours without cracking or fracture according to NACE™ 0177 A method, and no cracks appear after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

[0012] In a sixth aspect, the present invention provides a 60ksi grade anti-sulfur oil casing, wherein the 60ksi grade anti-sulfur oil casing comprises the following chemical components in weight percentages: C 0.12%~0.15%, Si 0.17%~0.25%, Mn 1.05%~1.15%, P 0.008%~0.011%, S 0.0015%~0.0017%, Al 0.015%~0.018%, Ca 0.007%~0.010%, N 0.0035%~0.0045%, O 0.0016%~0.0017%, H 0.00011%~0.00013%, Cr 0.15%~0.20%, V 0.035%~0.045%, RE 0.0025%~0.0050%, balance Fe and unavoidable impurities; The metallographic structure of the 60ksi grade oil casing is acicular ferrite and granular bainite, with a grain size of 10.0-11.0. The yield strength is 470-490 MPa, the tensile strength is 595-620 MPa, the elongation is 34%-35%, and the transverse Charpy V-notch impact energy at 0℃ is 85-104 J. It can withstand 95% of the specified minimum yield strength in solution A for 720 hours without cracking or fracture according to NACE™ 0177 A method. It also shows no cracking after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

[0013] A seventh aspect of the present invention provides a method for preparing the 60ksi steel-grade anti-sulfur oil casing as described above, comprising the following steps: Based on the chemical composition of 60ksi grade anti-sulfur oil casing, after batching, smelting, and continuous casting, a continuously cast billet is obtained. The continuously cast bar billet is subjected to hot piercing and hot continuous rolling, then controlled rolling with fixed diameter reduction, followed by controlled cooling and online self-tempering to obtain a tube billet. After hot straightening the tube blank, the 60ksi grade sulfur-resistant oil casing is obtained.

[0014] Optionally, before hot piercing the continuously cast billet, a segmented heating step is further included, wherein the process parameters for the segmented heating are as follows: The preheating section temperature is ≤900℃; the heating section temperature is 1100~1200℃; the soaking section temperature is 1230~1280℃, and the soaking section holding time is 150~240min; The temperature used for the thermal piercing is 1150–1220℃, and the piercing ratio is 3.0–4.0. The process parameters for the hot continuous rolling are as follows: The rolling temperature is 1050~1150℃, and the total rolling deformation is ≥70%.

[0015] Optionally, the process parameters for fixed-diameter reduction and controlled rolling are as follows: The temperature before the diameter reduction is 950-1050℃, the cumulative deformation during diameter reduction is 20%-40%, and the final rolling temperature is 850-950℃. The process parameters for controlling cooling are as follows: The inner and outer surfaces of the tube are cooled simultaneously. The initial cooling temperature is 850–950℃, the final cooling temperature is 450–600℃, and the cooling rate is 10–50℃ / s.

[0016] Optionally, the process parameters for online self-tempering are as follows: The self-tempering temperature is 500–650℃, and the self-tempering time is 30–120s; The temperature for hot straightening is 450–610℃.

[0017] Beneficial effects: The 60ksi grade sulfur-resistant oil casing provided by this invention has a yield strength of 414-552MPa, a tensile strength ≥552MPa, an elongation of 31%-35%, and a transverse Charpy V-notch impact energy ≥80J at 0℃. The metallographic structure is acicular ferrite + granular bainite with a grain size of 10.0-11.5. It does not exhibit cracking or fracture after 720 hours of testing in solution A with 95% of the specified minimum yield strength (SMYS) stress level (393MPa) according to NACE TM 0177 A method. It also shows no cracking after 96 hours of testing in saturated H2S solution according to NACE TM 0284, demonstrating excellent sulfur resistance (resistance to H2S stress corrosion and hydrogen-induced cracking). Detailed Implementation

[0018] This invention provides a 60ksi grade anti-sulfur oil casing and its preparation method. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.

[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0020] If the embodiments of the present invention involve descriptions such as "first" or "second", such descriptions are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated.

[0021] This invention provides a 60ksi grade sulfur-resistant oil casing, specifically a D60SS oil casing. D60 represents the steel grade designation, specifying a minimum yield strength ≥60ksi (or 414MPa); SS indicates a super sulfur-resistant variety. The D60SS oil casing comprises the following chemical components by mass percentage: C 0.10%~0.15%, Si 0.17%~0.37%, Mn 1.05%~1.28%, P≤0.012%, S≤0.003%, Al0.010%~0.018%, Ca 0.007%~0.015%, N≤0.005%, O≤0.002%, H≤0.00015%, Cr 0.15%~0.25%, V 0.035%~0.060%, RE 0.001%~0.005%, balance Fe and unavoidable impurities.

[0022] In this embodiment, the D60SS oil casing has a yield strength of 414–552 MPa, a tensile strength ≥552 MPa, an elongation of 31%–35%, a transverse Charpy V-notch impact energy ≥80 J at 0℃, and a microstructure of acicular ferrite + granular bainite with a grain size of 10.0–11.5. It does not exhibit cracking or fracture after 720 hours of testing in solution A with 95% of the specified minimum yield strength (SMYS) stress level (393 MPa) according to NACE™ 0177 A method. It also does not show cracking after 96 hours of testing in saturated H2S solution according to NACE™ 0284, demonstrating good sulfur resistance (resistance to H2S stress corrosion and hydrogen-induced cracking).

[0023] RE stands for rare earth element. In some specific embodiments, RE can be Ce (cerium).

[0024] To simultaneously meet the multiple requirements of strength, toughness, resistance to H2S stress corrosion and hydrogen-induced cracking, and economy in oil casing, the chemical composition of the oil casing must be rationally designed. Specifically, this invention proposes to adopt a low-C, low-Mn, and low-Cr alloy design, combined with Mn-Cr-V-RE composite alloying and micro-alloying, using Al and Si full deoxidation, strictly controlling the content of impurities and harmful gas elements such as P, S, O, H, and N in the steel, adding RE, and treating the molten steel with Ca, and using appropriate processing and preparation techniques. The process yields a multiphase microstructure dominated by fine-grained acicular ferrite and granular bainite, resulting in oil casing products that combine high strength (yield strength of 414–552 MPa, tensile strength ≥552 MPa), good low-temperature toughness (0℃ transverse Charpy V-notch impact energy ≥80 J), and excellent sulfur resistance (passing NACE tests for H2S stress corrosion and hydrogen-induced cracking). This achieves a balance between cost reduction and high performance, meeting the demand for economical D60SS oil casing in H2S-containing oil and gas field development.

[0025] The roles and content ranges of each element are as follows: C (Carbon): Carbon is a fundamental element for ensuring strength, but excessive content can worsen sulfur resistance and toughness. This invention employs a low-carbon design, which is beneficial for improving ductility, toughness, and corrosion resistance. The lower limit of 0.10% ensures matrix strength, while the upper limit of 0.15% avoids excessive carbide precipitation that could lead to a decrease in toughness and sulfur resistance. Considering all factors, it is advisable to control the carbon content within the range of 0.10% to 0.15%.

[0026] Si (Silicon): Silicon is added as a deoxidizer and also has a certain solid solution strengthening effect. Taking all factors into consideration, controlling the content within the range of 0.17% to 0.37% can ensure the deoxidation effect while avoiding excessive silicon content from deteriorating toughness.

[0027] Mn (Manganese): Manganese is an important strengthening element that can lower the phase transformation temperature and refine the microstructure. This invention employs a low manganese content design, which improves hardenability while reducing segregation, thereby improving corrosion resistance. It also works synergistically with Cr and V to promote the formation of acicular ferrite. Considering all factors, the manganese content should ideally be controlled within the range of 1.05% to 1.28%.

[0028] Cr (chromium): Chromium is one of the key alloying elements. Cr can significantly improve the hardenability of steel, delay the pearlite transformation, and promote the formation of acicular ferrite / bainite; at the same time, Cr can refine carbides, improve tempering stability, and enhance strength and toughness. Meanwhile, the addition of Cr can improve the corrosion resistance of steel in environments containing H2S and CO2. Considering all factors, controlling the Cr content within the range of 0.15% to 0.25% can both exert its beneficial effects and avoid the increased cost caused by excessively high Cr content.

[0029] Vanadium (V): Vanadium is another key microalloying element. During heating and rough rolling, undissolved VN or V(C,N) particles can refine the original austenite grains through pinning effect, thereby causing the refinement of recrystallized grains during rolling. During finish rolling, V can regulate the recrystallization of austenite, accumulate deformation, and refine the microstructure. During the cooling process after rolling, V precipitates in large quantities in the form of nano-sized VN or V(C,N) particles, playing a precipitation strengthening role. At the same time, the formation of VN or V(C,N) is beneficial to eliminate free N, improve the strain aging properties of N, and improve the uniformity and stability of material properties. The combined addition of V and Cr can more effectively delay the high-temperature transformation and expand the formation window of acicular ferrite. Taking all factors into consideration, it is advisable to control it within the range of 0.035% to 0.060%.

[0030] P (phosphorus) and S (sulfur): Phosphorus and sulfur are harmful impurity elements that can significantly deteriorate corrosion resistance and toughness. Taking all factors into consideration, it is advisable to control P ≤ 0.012% (i.e., P mass percentage less than or equal to 0.012%) and S ≤ 0.003% (i.e., S mass percentage less than or equal to 0.003%).

[0031] Nitrogen (N), hydrogen (H), and oxygen (O): These are harmful gaseous elements that significantly deteriorate corrosion resistance and toughness. Considering all factors, it is advisable to control N ≤ 0.005%, O ≤ 0.002%, and H ≤ 0.00015%.

[0032] Al (aluminum): Aluminum is used for deoxidation and grain refinement. It combines with nitrogen to form AlN, inhibiting austenite grain growth and suppressing the strain aging phenomenon of nitrogen. It is advisable to control the Al / N ratio to be ≥2 (i.e., the ratio of the mass percentage of Al to the mass percentage of N is greater than or equal to 2). Considering all factors, it is advisable to control it within the range of 0.010% to 0.018%.

[0033] Ca (calcium): Calcium is used for inclusion modification treatment, transforming elongated MnS into spherical composite sulfides, thus improving corrosion resistance and toughness. The effect is better when Ca / S ≥ 2. Considering all factors, it is advisable to control the concentration within the range of 0.007% to 0.015%.

[0034] Rare earth elements (RE): Rare earth elements can purify grain boundaries and improve the morphology of inclusions, which can further enhance corrosion resistance and toughness. Considering all factors, the concentration should be controlled within the range of 0.001% to 0.005%.

[0035] In some embodiments, the D60SS casing comprises the following chemical components in weight percentages: C 0.10%~0.15%, Si 0.17%~0.37%, Mn 1.05%~1.28%, P 0.008%~0.012%, S 0.0015%~0.0020%, Al 0.010%~0.018%, Ca 0.007%~0.015%, N 0.0035~0.0045%, O 0.0015%~0.0019%, H 0.00010%~0.00014%, Cr 0.15%~0.25%, V 0.035%~0.060%, RE 0.001%~0.005%, balance Fe and unavoidable impurities.

[0036] In this embodiment, the D60SS oil casing has a yield strength of 470–535 MPa, a tensile strength of 595–665 MPa, an elongation of 31%–35%, a transverse Charpy V-notch impact energy of 85–112 J at 0°C, and a metallographic structure of acicular ferrite + granular bainite with a grain size of 10.0–11.5. It does not crack or fracture after 720 hours of testing in solution A with 95% of the specified minimum yield strength (SMYS) stress level (393 MPa) according to NACE™ 0177 A method. It also does not crack after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

[0037] In some embodiments, the D60SS casing comprises the following chemical components in weight percentages: C 0.10%~0.13%, Si 0.25%~0.37%, Mn 1.15%~1.28%, P 0.008%~0.012%, S 0.0015~0.0020%, Al 0.010%~0.015%, Ca 0.010%~0.015%, N 0.0035%~0.0042%, O 0.0015%~0.0019%, H 0.00010%~0.00014%, Cr 0.18%~0.25%, V 0.045%~0.060%, RE 0.0010%~0.0035%, balance Fe and unavoidable impurities.

[0038] In this embodiment, the D60SS oil casing has a yield strength of 490–535 MPa, a tensile strength of 620–665 MPa, an elongation of 31%–34%, a transverse Charpy V-notch impact energy of 96–112 J at 0°C, and a metallographic structure of acicular ferrite + granular bainite with a grain size of 10.5–11.5. It does not crack or fracture after 720 hours of testing in solution A with 95% of the specified minimum yield strength (SMYS) stress level (393 MPa) according to NACE™ 0177 A method. It also does not crack after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

[0039] In some embodiments, the D60SS casing comprises the following chemical components in weight percentages: C 0.10%~0.13%, Si 0.28%~0.37%, Mn 1.18%~1.28%, P 0.009%~0.012%, S 0.002%, Al 0.010%~0.014%, Ca 0.011%~0.015%, N 0.0038%~0.0042%, O 0.0015%~0.0019%, H 0.00010%~0.00014%, Cr 0.18%~0.25%, V 0.048%~0.060%, RE 0.0010%~0.0035%, balance Fe and unavoidable impurities.

[0040] In this embodiment, the D60SS oil casing has a yield strength of 510–535 MPa, a tensile strength of 635–665 MPa, an elongation of 31%–33%, a transverse Charpy V-notch impact energy of 96–112 J at 0°C, and a metallographic structure of acicular ferrite + granular bainite with a grain size of 10.5–11.5. It does not crack or fracture after 720 hours of testing in solution A with 95% of the specified minimum yield strength (SMYS) stress level (393 MPa) according to NACE TM 0177 A method. It also does not crack after 96 hours of testing in saturated H2S solution according to NACE TM 0284.

[0041] In some embodiments, the D60SS casing comprises the following chemical components in weight percentages: C 0.11%~0.13%, Si 0.28%~0.32%, Mn 1.18%~1.22%, P 0.009%~0.010%, S 0.002%, Al 0.012%~0.014%, Ca 0.011%~0.012%, N 0.0038%~0.0040%, O 0.0015%~0.0019%, H 0.00010%~0.00014%, Cr 0.23%~0.25%, V 0.048%~0.055%, RE 0.0030%~0.0035%, balance Fe and unavoidable impurities.

[0042] In this embodiment, the D60SS oil casing has a yield strength of 525–535 MPa, a tensile strength of 650–665 MPa, an elongation of 31%–32%, a transverse Charpy V-notch impact energy of 96–100 J at 0°C, and a metallographic structure of acicular ferrite + granular bainite with a grain size of 10.5–11.0. It does not crack or fracture after 720 hours of testing in solution A with 95% of the specified minimum yield strength (SMYS) stress level (393 MPa) according to NACE™ 0177 A method. It also does not crack after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

[0043] In some embodiments, the D60SS casing comprises the following chemical components in weight percentages: C 0.12%~0.15%, Si 0.17%~0.25%, Mn 1.05%~1.15%, P 0.008%~0.011%, S 0.0015%~0.0017%, Al 0.015%~0.018%, Ca 0.007%~0.010%, N 0.0035%~0.0045%, O 0.0016%~0.0017%, H 0.00011%~0.00013%, Cr 0.15%~0.20%, V 0.035%~0.045%, RE 0.0025%~0.0050%, balance Fe and unavoidable impurities.

[0044] In this embodiment, the D60SS oil casing has a yield strength of 470–490 MPa, a tensile strength of 595–620 MPa, an elongation of 34%–35%, a transverse Charpy V-notch impact energy of 85–104 J at 0°C, and a metallographic structure of acicular ferrite + granular bainite with a grain size of 10.0–11.0. It does not exhibit cracks or fractures after 720 hours of testing in solution A with 95% of the specified minimum yield strength (SMYS) stress level (393 MPa) according to NACE™ 0177 A method. Furthermore, it does not show cracks after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

[0045] In some embodiments, the D60SS casing comprises the following chemical components by weight percentage: C 0.10%~0.13%, Si 0.25%~0.37%, Mn 1.15%~1.28%, P 0.008-0.012%, S 0.0015-0.0020%, Al 0.010%~0.015%, Ca 0.010%~0.015%, N 0.0035-0.0042%, O 0.0015-0.0018%, H 0.00010-0.00013%, Cr 0.18%~0.23%, V 0.045%~0.060%, RE 0.0010%~0.0035%, balance Fe and unavoidable impurities.

[0046] In this embodiment, the D60SS oil casing has a yield strength of 490–525 MPa, a tensile strength of 620–650 MPa, an elongation of 32%–34%, a transverse Charpy V-notch impact energy of 96–112 J at 0°C, and a metallographic structure of acicular ferrite + granular bainite with a grain size of 10.5–11.5. It does not crack or fracture after 720 hours of testing in solution A with 95% of the specified minimum yield strength (SMYS) stress level (393 MPa) according to NACE™ 0177 A method. It also does not crack after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

[0047] This invention develops a matching manufacturing process for the chemical composition with the aforementioned proportions. This process mainly involves pure steel smelting, continuous casting, hot rolling in the austenitic region, controlled rolling with large deformation (rolling deformation ≥70%), and controlled cooling + online self-tempering to obtain a fine-grained microstructure of acicular ferrite and granular bainite. This results in oil casing products with high strength (yield strength 414–552 MPa, tensile strength ≥552 MPa), good low-temperature toughness (0℃ transverse Charpy V-notch impact energy ≥80 J), and excellent sulfur resistance (passing NACE H2S stress corrosion and hydrogen-induced cracking tests), achieving a balance between cost reduction and high-quality performance.

[0048] Specifically, embodiments of the present invention provide a method for preparing the D60SS oil casing as described above, comprising the following steps: S1. Based on the chemical composition of the D60SS oil casing, the raw materials are prepared, smelted, and continuously cast to obtain a continuously cast billet. S2. The continuously cast bar billet is subjected to hot piercing and hot continuous rolling, then controlled rolling with fixed diameter reduction, followed by controlled cooling and online self-tempering to obtain a tube billet. S3. After hot straightening the tube blank, the D60SS oil casing is obtained.

[0049] The D60SS oil casing prepared by the method provided in this invention exhibits high strength, good low-temperature toughness, and resistance to H2S stress corrosion and hydrogen-induced cracking. The oil casing has a yield strength of 414–552 MPa, a tensile strength ≥552 MPa, an elongation of 31%–35%, and a transverse Charpy V-notch impact energy ≥80 at 0℃. Its microstructure consists of acicular ferrite and granular bainite with a grain size of 10.0–11.5. Following NACE™ 0177 A method, it undergoes a 720-hour test in solution A with 95% of the specified minimum yield strength (SMYS) stress level (393 MPa) without cracking or fracture. Following NACE™ 0284 method, it undergoes a 96-hour test in a saturated H2S solution without cracking. Furthermore, it has a low cost.

[0050] This invention achieves a balance of strength, toughness, and sulfur resistance in oil casing pipes by comprehensively utilizing pure steel preparation, fine grain strengthening and toughening, precipitation strengthening, phase transformation strengthening, controlled rolling and cooling, and online self-tempering, under the premise of low C, low Mn, and small amount of Cr, and without quenching and tempering (low cost).

[0051] 1) Refined Grain Strength and Toughness: Austenite grain refinement is achieved under final rolling conditions through the synergistic effect of large deformation controlled rolling (≥70%) and V microalloying. The pinning effect of undissolved VN or V(C,N) provides fine original austenite grains. Repeated dynamic recrystallization during the rolling stage further refines the grains. During deformation, strain-induced precipitation of VN or V(C,N) inhibits austenite recrystallization and accumulates deformation energy. After phase transformation, fine acicular ferrite / granular bainite structure is obtained, which can improve both strength and toughness.

[0052] 2) Precipitation strengthening: Nanoscale carbonitrides of V are dispersed and precipitated in large quantities during rolling and cooling, providing a significant precipitation strengthening effect. The addition of Cr promotes the formation of fine carbides and enhances the precipitation strengthening effect.

[0053] 3) Phase transformation strengthening: By controlling the cooling path, a acicular ferrite / granular bainite multiphase structure is obtained, and the strength is improved by phase transformation strengthening. The addition of Cr delays the pearlite transformation and expands the acicular ferrite formation window, which is conducive to obtaining an ideal structure.

[0054] 4) Online self-tempering mechanism: During controlled cooling, the surface layer of the steel pipe undergoes a phase transformation after rapid cooling. The residual heat from the uncooled core is then used to perform self-tempering on the surface layer, further spheroidizing and dispersing the carbides, thus eliminating internal stress and improving sulfur resistance. The addition of Cr enhances tempering stability, making the self-tempering effect even more significant.

[0055] 5) Anti-sulfur mechanism: Non-coplanar dislocation groups, fine precipitates, and dispersed high-sphericity carbides give steel excellent resistance to H2S stress corrosion and hydrogen-induced cracking. The fine-grained structure obtained through controlled rolling and cooling in this invention features uniform dislocation distribution and fine, dispersed carbides, effectively reducing susceptibility to hydrogen-induced cracking. Simultaneously, the addition of Cr increases the electrode potential of the steel, improving corrosion resistance; strict control of impurities and harmful gaseous elements such as P, S, O, H, and N improves the purity of the steel; and the addition of Ca and RE improves the morphology of inclusions and reduces hydrogen trapping.

[0056] In step S1, in some implementations, the steps of preparing, smelting, and continuously casting the D60SS oil casing according to its chemical composition to obtain the continuously cast billet specifically include: The raw materials for the D60SS oil casing are prepared according to their chemical composition. The process involves smelting in a converter or electric furnace, followed by refining in an LF furnace (ladle refining furnace) and treatment with VD (vacuum degassing) or RH (vacuum circulating degassing), with strict control over the P, S, O, N, and H contents. During smelting or continuous casting, Ca and RE treatments are performed to modify inclusions. The billets are then continuously cast into round bars, employing electromagnetic stirring and light reduction techniques to improve their internal quality.

[0057] In step S2, in some embodiments, a segmented heating step is included before hot piercing the continuously cast billet. The process parameters for the segmented heating are as follows: The preheating section temperature is ≤900℃; the heating section temperature is 1100~1200℃; the soaking section temperature is 1230~1280℃, and the soaking section holding time is 150~240min to ensure that the reduced elements are fully dissolved.

[0058] In some embodiments, a conical piercing machine is used for hot piercing. During the piercing process, the uniformity of the steel pipe wall thickness and the quality of the inner and outer surfaces are strictly controlled. The temperature used for hot piercing is 1150-1220℃, and the piercing ratio is 3.0-4.0.

[0059] In some implementations, a two- or three-roll mandrel continuous rolling mill is used for rolling. Tension control is employed during the hot continuous rolling process to ensure the accuracy of the steel pipe wall thickness. Through continuous large deformation over multiple stands, combined with V-microalloying, deformation energy is accumulated for austenite grain refinement. Specifically, the process parameters for the hot continuous rolling are as follows: The rolling temperature is 1050~1150℃, and the total rolling deformation is ≥70%.

[0060] In some implementations, controlled rolling is performed in the diameter reduction process, and the process parameters for diameter reduction and controlled rolling are as follows: The temperature before the sizing and reduction is 950-1050℃, the cumulative deformation during sizing and reduction is 20%-40% (which can be completed in 2-4 stands), and cooling is performed between passes (a cooling device is installed between the sizing and reduction stands to rapidly cool the steel pipe between passes, achieving precise control of the rolling temperature). The final rolling temperature is 850-950℃ (to ensure that the rolling enters the two-phase region and promotes grain refinement).

[0061] Rapid cooling between passes allows for immediate adjustment of the rolled piece temperature, accumulating deformation energy and creating conditions for subsequent phase transformation refinement.

[0062] In some implementations, controlled cooling is performed immediately after final rolling, employing head-and-tail shielding and rotary cooling techniques to ensure uniform temperature along the entire length and circumference of the steel pipe. Specifically, the process parameters for controlled cooling are as follows: The inner and outer surfaces of the tube are cooled simultaneously. The initial cooling temperature is 850–950℃, and the final cooling temperature is 450–600℃ (adjusted according to wall thickness and target microstructure). The cooling rate is 10–50℃ / s (the cooling rate is adjusted according to the wall thickness of the oil jacket: 30–50℃ / s when the wall thickness is ≤10mm; 20–30℃ / s when the wall thickness is 10mm<20mm; and 10–20℃ / s when the wall thickness is ≥20mm). Cooling uniformity is also controlled (overall / circumferential temperature control accuracy is ±20℃).

[0063] In this embodiment, the outer and inner surfaces of the steel pipe are cooled simultaneously. The cooling device includes an outer spray ring and an inner spray gun. The steel pipe rotates and moves forward during the cooling process to achieve uniform cooling of the entire length (10-36m).

[0064] In some implementations, after the surface of the steel pipe cools to its final cooling temperature, forced cooling is stopped, and the residual heat from the core of the steel pipe is used to perform self-tempering treatment on the surface, causing the carbides to spheroidize and disperse, thus eliminating internal stress. The process parameters for online self-tempering are as follows: The self-tempering temperature is 500–650℃, and the self-tempering time is 30–120s (the online self-tempering time is adjusted according to the wall thickness of the oil casing: when the wall thickness is ≤10mm, the self-tempering time is 30–60s; when the wall thickness is 10mm<20mm, the self-tempering time is 60–90s; when the wall thickness is ≥20mm, the self-tempering time is 90–120s). Self-tempering further spheroidizes and disperses carbides in the surface phase transformation microstructure, eliminating internal stress and improving sulfur resistance. The addition of Cr improves the tempering stability of the steel and allows for more complete spheroidization of carbides during the self-tempering process.

[0065] In some implementations, after online self-tempering, the air is cooled to room temperature before hot straightening is performed at a temperature of 450–610°C.

[0066] After hot straightening, finishing processes such as non-destructive testing, thread machining, magnetic particle inspection, and hydrostatic testing can be performed.

[0067] The present invention will be further described below through specific embodiments.

[0068] Table 1. Chemical composition of the casing and tubing in each embodiment and comparative example.

[0069] In Table 1, the content of each component is by mass percentage, with the remainder being Fe and unavoidable impurities up to 100%. "-" indicates that the element is not present.

[0070] Example 1 This embodiment provides a D60SS oil casing and its preparation method.

[0071] The chemical composition of the D60SS oil casing is shown in Example 1 of Table 1.

[0072] The preparation method of D60SS oil casing includes the following steps: (1) Smelting and continuous casting: The oil casing of Example 1 was prepared according to the chemical composition shown in Table 1. It was smelted in a 120t converter, refined in an LF furnace for 40 minutes, fed with Ce wire, vacuum degassing for 25 minutes, vacuum degree ≤67Pa, fed with Ca wire, and continuously cast into Φ210mm round billet. The continuous casting process adopted electromagnetic stirring and light reduction technology.

[0073] (2) Heating of round bar billet: segmented heating control, the temperature of the preheating section is ≤900℃, the temperature of the heating section is 1100~1200℃, the temperature of the soaking section is 1250℃, and the soaking section is kept warm for 180min.

[0074] (3) Hot piercing: The heated round bar billet is hot pierced using a conical piercing machine. The hot piercing temperature is 1180℃ and the piercing ratio is 3.5.

[0075] (4) Hot continuous rolling: The hot continuous rolling is carried out using a three-roll limited mandrel continuous rolling mill. The rolling temperature is 1100℃, and the tube is rolled into a rough tube of Φ177.8mm×10mm. The total rolling deformation is 72%.

[0076] (5) Sizing and control rolling: The temperature before sizing and reducing the diameter is 1000℃. After sizing and reducing the diameter in 3 stands, the cumulative deformation is 30%. Water cooling is used between stands (rapid cooling between passes for the steel pipe). The final rolling temperature is 900℃.

[0077] (6) Controlled cooling and online self-tempering: Head and tail shielding and rotation cooling technology are adopted. The steel pipe rotates forward during the cooling process to ensure uniform cooling. The starting cooling temperature is 900℃, and external spraying + internal spraying is used for cooling. The cooling rate is 35℃ / s, and the final cooling temperature is 480℃. The self-tempering temperature is 520℃, and the self-tempering time is 60s.

[0078] (7) Air cooling: After tempering, air cool to room temperature.

[0079] (8) Straightening and finishing: straightening at 470°C with a seven-roll straightener, ultrasonic testing, processing of connecting threads at the pipe ends and magnetic particle testing and hydrostatic testing.

[0080] Example 2 This embodiment provides a D60SS oil casing and its preparation method.

[0081] The chemical composition of the D60SS oil casing is shown in Example 2 of Table 1.

[0082] The preparation method of D60SS oil casing includes the following steps: (1) Smelting and continuous casting: The oil casing of Example 2 was prepared according to the chemical composition shown in Table 1, smelted in an electric furnace, refined in an LF furnace for 45 min, fed with Ce wire, vacuum degassing for 30 min, vacuum degree ≤67 Pa, fed with Ca wire, and continuously cast into Φ270mm round billet. The continuous casting process adopted electromagnetic stirring and light reduction technology.

[0083] (2) Heating of round bar billet: segmented heating control, the temperature of the preheating section is ≤900℃, the temperature of the heating section is 1100~1200℃, the temperature of the soaking section is 1260℃, and the soaking section is held for 240min.

[0084] (3) Hot piercing: The heated round bar billet is hot pierced using a conical piercing machine. The hot piercing temperature is 1190℃ and the piercing ratio is 3.8.

[0085] (4) Hot continuous rolling: The hot continuous rolling is carried out using a three-roll limited mandrel continuous rolling mill. The rolling temperature is 1120℃, and the tube is rolled into a rough tube of Φ244.5mm×12mm. The total rolling deformation is 74%.

[0086] (5) Sizing and control rolling: The temperature before sizing and reducing the diameter is 980℃. After 4 stands for sizing and reducing the diameter, the cumulative deformation is 35%. Water cooling is used for cooling between stands (rapid cooling between passes of the steel pipe). The final rolling temperature is 880℃.

[0087] (6) Controlled cooling and online self-tempering: Head and tail shielding and rotation cooling technology are adopted. The steel pipe rotates forward during the cooling process to ensure uniform cooling. The starting cooling temperature is 880℃. External spraying + internal spraying is used for cooling. The cooling rate is 20℃ / s and the final cooling temperature is 460℃. The self-tempering temperature is 540℃ and the self-tempering time is 80s.

[0088] (7) Air cooling: After tempering, air cool to room temperature.

[0089] (8) Straightening and finishing: straightening at 490°C with a seven-roll straightener, ultrasonic testing, processing of connecting threads at the pipe ends and magnetic particle testing and hydrostatic testing.

[0090] Example 3 (Thin-wall specification) This embodiment provides a D60SS oil casing and its preparation method.

[0091] The chemical composition of the D60SS oil casing is shown in Example 3 of Table 1.

[0092] The preparation method of D60SS oil casing includes the following steps: (1) Smelting and continuous casting: The only difference from step (1) in Example 1 is that the raw materials are prepared according to the chemical composition of the oil casing of Example 3 shown in Table 1; and continuously cast into Φ150mm round billet.

[0093] (2) Heating of round bar billet: Same as step (2) in Example 1.

[0094] (3) Thermal perforation: Same as step (3) in Example 1.

[0095] (4) Hot rolling: The only difference from step (4) in Example 1 is that it is rolled into a rough tube of Φ114.3mm×6mm with a total rolling deformation of 76%.

[0096] (5) Fixed diameter reduction and controlled rolling: Same as step (5) in Example 1.

[0097] (6) Controlled cooling and online self-tempering: The only difference from step (6) in Example 1 is that the cooling rate is 40℃ / s, the final cooling temperature is 500℃, the self-tempering temperature is 550℃, and the self-tempering time is 40s.

[0098] (7) Air cooling: Same as step (7) in Example 1.

[0099] (8) Straightening and finishing: The only difference from step (8) in Example 1 is that the seven-roll straightener is used for straightening at 500°C.

[0100] Example 4 (Thick-walled specification) This embodiment provides a D60SS oil casing and its preparation method.

[0101] The chemical composition of the D60SS oil casing is shown in Example 4 of Table 1.

[0102] The preparation method of D60SS oil casing includes the following steps: (1) Smelting and continuous casting: The only difference from step (1) in Example 2 is that the raw materials are prepared according to the chemical composition of the oil casing of Example 4 shown in Table 1; and continuously cast into Φ310mm round billet.

[0103] (2) Heating of round bar billet: Same as step (2) in Example 2.

[0104] (3) Thermal perforation: Same as step (3) in Example 2.

[0105] (4) Hot rolling: The only difference from step (4) in Example 2 is that the tube is rolled into a rough tube of Φ273.1mm×20mm with a total rolling deformation of 70%.

[0106] (5) Fixed diameter reduction and controlled rolling: Same as step (5) in Example 2.

[0107] (6) Controlled cooling and online self-tempering: The only difference from step (6) in Example 2 is that the cooling rate is 12℃ / s, the final cooling temperature is 550℃, the self-tempering temperature is 600℃, and the self-tempering time is 110s.

[0108] (7) Air cooling: Same as step (7) in Example 2.

[0109] (8) Straightening and finishing: The only difference from step (8) in Example 2 is that the seven-roll straightener is used for straightening at 550°C.

[0110] Example 5 This embodiment provides a D60SS oil casing and its preparation method.

[0111] The chemical composition of the D60SS oil casing is shown in Example 5 of Table 1.

[0112] The preparation method of D60SS oil casing includes the following steps: (1) Smelting and continuous casting: The only difference from step (1) in Example 1 is that the ingredients are prepared according to the chemical composition of the oil casing of Example 5 shown in Table 1.

[0113] (2) Heating of round bar billet: segmented heating control, the temperature of the preheating section is ≤900℃, the temperature of the heating section is 1100~1200℃, the temperature of the soaking section is 1250℃, and the soaking section is kept warm for 180min.

[0114] (3) Thermal perforation: Same as step (3) in Example 1.

[0115] (4) Hot rolling: Same as step (4) in Example 1.

[0116] (5) Fixed diameter reduction and controlled rolling: The only difference from step (5) in Example 1 is that the final rolling temperature is 860℃.

[0117] (6) Controlled cooling and online self-tempering: The only difference from step (6) in Example 1 is that the cooling rate is 30℃ / s, the final cooling temperature is 450℃, the self-tempering temperature is 500℃, and the self-tempering time is 55s.

[0118] (7) Air cooling: Same as step (7) in Example 1.

[0119] (8) Straightening and finishing: The only difference from step (8) in Example 1 is that the seven-roll straightener is used for straightening at 450°C.

[0120] Comparative Example 1 (high content of C, Mn, Si, P, S, N, O and H, low content of Ce, no Cr and V in the composition, no Ca treatment, air-cooled after rolling) This comparative example provides an oil casing and its preparation method.

[0121] The chemical composition of the oil casing is shown in Comparative Example 1 in Table 1.

[0122] The preparation method of the oil casing includes the following steps: (1) Smelting and continuous casting: The oil casing of Comparative Example 1 was prepared according to the chemical composition shown in Table 1. It was smelted in a 120t converter, refined in an LF furnace for 40 minutes, fed with Ce wire, and vacuum degassing for 25 minutes with a vacuum degree ≤67Pa. It was then continuously cast into Φ210mm round billets. Electromagnetic stirring and light reduction technology were used in the continuous casting process.

[0123] (2) Heating of round bar billet: Same as step (2) in Example 1.

[0124] (3) Thermal perforation: Same as step (3) in Example 1.

[0125] (4) Hot continuous rolling: The three-roll limited mandrel continuous rolling mill is used for continuous rolling. The initial rolling temperature is 1100℃ and the final rolling temperature is 900℃. The tube is rolled into a rough tube of Φ177.8mm×10mm with a total rolling deformation of 55%. After rolling, the tube is air-cooled to room temperature.

[0126] (5) Straightening and finishing: Same as step (8) in Example 1.

[0127] Comparative Example 2 (high content of C, Mn, P, S, Al, N, O and H, low content of Cr, no Ca treatment, air-cooled after rolling) This comparative example provides an oil casing and its preparation method.

[0128] The chemical composition of the oil casing is shown in Comparative Example 2 in Table 1.

[0129] The preparation method of the oil casing is basically the same as that of Comparative Example 1, except that the ingredients are prepared according to the chemical composition of the oil casing of Comparative Example 2 shown in Table 1.

[0130] Comparative Example 3 (insufficient rolling deformation, no controlled cooling, and no self-tempering process) This comparative example provides an oil casing and its preparation method.

[0131] The chemical composition of the oil casing is shown in Comparative Example 3 in Table 1.

[0132] The only difference between the preparation method of the oil casing and the Example 1 is that the materials are prepared according to the chemical composition of the oil casing of Comparative Example 3 shown in Table 1; the rolling deformation is 55% and the material is directly air-cooled from the final rolling temperature to room temperature (without controlled cooling and online self-tempering), and the rest is the same as Example 1.

[0133] Comparative Example 4 (no Cr in its composition) This comparative example provides an oil casing and its preparation method.

[0134] The chemical composition of the oil casing is shown in Comparative Example 4 in Table 1.

[0135] The preparation method of the oil casing is the same as that of Example 1, except that the ingredients are prepared according to the chemical composition of the oil casing of Comparative Example 4 shown in Table 1.

[0136] Comparative Example 5 (no V, no Ca, Ce treatment) This comparative example provides an oil casing and its preparation method.

[0137] The chemical composition of the oil casing is shown in Comparative Example 5 in Table 1.

[0138] The preparation method of the oil casing differs from that of Example 1 only in that: step (1) is specifically to prepare the raw materials according to the chemical composition of the oil casing of Comparative Example 5 shown in Table 1, smelt in a 120t converter, refine in an LF furnace for 40 minutes, degas under vacuum for 25 minutes, with a vacuum degree ≤67Pa, and continuously cast into Φ210mm round billets. The continuous casting process adopts electromagnetic stirring and light reduction technology. The remaining steps are the same as those in Example 1.

[0139] The oil casing in each embodiment and comparative example was tested, and the results are shown in Table 2.

[0140] Table 2. Test results of oil casing in the examples and comparative examples.

[0141] Note: The technical requirements for D60SS oil casing in this invention are as follows: yield strength 414~552MPa; tensile strength ≥552MPa; elongation ≥20%; transverse Charpy V-notch impact energy at 0℃ ≥80J; NACE™ 0284 hydrogen-induced cracking test: crack length ratio CLR≤10%, crack thickness ratio CTR≤3%, crack sensitivity ratio CSR≤1.5%; NACE™ 0177 A method A solution H2S stress corrosion test: loading 95% of the specified minimum yield strength (393MPa) for 720h, without cracking or fracture.

[0142] However, the typical requirements for sulfur-resistant oil casing are: NACE™ 0284 hydrogen-induced cracking test: crack length ratio (CLR) ≤ 15%; crack thickness ratio (CTR) ≤ 5%; crack susceptibility rate (CSR) ≤ 2%. NACE™ 0177 A-method A solution H2S stress corrosion test: loading 85% of the specified minimum yield strength (352 MPa) for 720 hours, without cracking or fracture.

[0143] The comparative results show that the casing provided by the embodiments of the present invention has excellent comprehensive performance, meeting both strength and toughness requirements, and passing the NACE sulfur resistance test. When the casings in the comparative examples differ from those in the embodiments in terms of deformation, self-tempering process, and composition control, their performance deteriorates. For example, the casings in Comparative Examples 1 and 2 have low toughness, and the sulfide inclusions are elongated; they failed the NACE™ 0177 A method A solution H2S stress corrosion test and the NACE™ 0284 saturated H2S hydrogen-induced cracking test. The casings in Comparative Examples 3 and 4 have low strength and toughness. The casing in Comparative Example 5 has low strength and toughness, and the sulfide inclusions are elongated; it failed the NACE™ 0177 A method A solution H2S stress corrosion test and the NACE™ 0284 saturated H2S hydrogen-induced cracking test.

[0144] In summary, this invention provides a 60ksi grade sulfur-resistant oil casing and its preparation method. Through an alloy design with low C, relatively low Mn, and a small amount of Cr, combined with Mn-Cr-V composite alloying and microalloying, pure steel smelting, large deformation controlled rolling (rolling deformation ≥70%), and controlled cooling + online self-tempering process, an oil casing product with high strength (yield strength of 414~552MPa, tensile strength ≥552MPa), good low-temperature toughness (transverse Charpy impact energy ≥80J at 0℃), and excellent sulfur resistance (passing NACE resistance to H2S stress corrosion and hydrogen-induced cracking tests) is obtained, achieving a balance between cost reduction and high performance.

[0145] Compared with the prior art, the present invention has the following technical effects: (1) Through the alloy design of low C-low Mn-small amount of Cr, combined with Mn-Cr-V-RE composite alloying and micro-alloying, the contents of P, S, N, H and O are strictly controlled, which significantly improves the sulfur resistance while ensuring strength and toughness and meets the requirements of NACE standard.

[0146] (2) The process of large deformation controlled rolling (≥70%) + controlled cooling + online self-tempering is adopted to replace the traditional offline heat treatment, eliminating the offline reheating quenching + tempering process, simplifying the production process, reducing energy consumption, and reducing the average energy consumption per ton of steel by more than 20 kg of standard coal.

[0147] (3) By controlling the cooling, a acicular ferrite / granular bainite multiphase structure is obtained, with the grain size increased by 1 to 3 levels compared with the traditional process, the impact energy increased by 20 to 50 J, and it has high strength (yield strength of 414 to 552 MPa, tensile strength ≥ 552 MPa), good toughness (0℃ impact energy ≥ 80 J) and excellent sulfur resistance.

[0148] (4) The online self-tempering process uses the residual heat of the core to temper the surface layer. The addition of Cr improves the tempering stability, makes the carbides more spheroidized and dispersed, and significantly improves the sulfur resistance compared with the traditional online cooling process.

[0149] (5) The product has excellent overall performance and lower cost than traditional anti-sulfur oil casing, giving it good market competitiveness.

[0150] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.

Claims

1. A 60ksi grade sulfur-resistant oil casing, characterized in that, The 60ksi grade anti-sulfur oil casing comprises the following chemical components by mass percentage: C 0.10%~0.15%, Si 0.17%~0.37%, Mn 1.05%~1.28%, P≤0.012%, S≤0.003%, Al0.010%~0.018%, Ca 0.007%~0.015%, N≤0.005%, O≤0.002%, H≤0.00015%, Cr 0.15%~0.25%, V 0.035%~0.060%, RE 0.001%~0.005%, balance Fe and unavoidable impurities; The metallographic structure of the 60ksi grade anti-sulfur oil casing consists of acicular ferrite and granular bainite with a grain size of 10.0–11.

5. Its yield strength is 414–552 MPa, tensile strength ≥552 MPa, elongation 31%–35%, and transverse Charpy V-notch impact energy ≥80 J at 0℃. It can withstand 95% loading at the specified minimum yield strength in solution A for 720 hours according to NACE™ 0177 A method without cracking or fracture. It also shows no cracking after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

2. A 60ksi grade sulfur-resistant oil casing, characterized in that, The 60ksi grade anti-sulfur oil casing comprises the following chemical components by mass percentage: C 0.10%~0.15%, Si 0.17%~0.37%, Mn 1.05%~1.28%, P 0.008%~0.012%, S 0.0015%~0.0020%, Al 0.010%~0.018%, Ca 0.007%~0.015%, N 0.0035~0.0045%, O 0.0015%~0.0019%, H 0.00010%~0.00014%, Cr 0.15%~0.25%, V 0.035%~0.060%, RE 0.001%~0.005%, balance Fe and unavoidable impurities; The metallographic structure of the 60ksi grade oil casing is acicular ferrite and granular bainite, with a grain size of 10.0–11.

5. The yield strength is 470–535 MPa, the tensile strength is 595–665 MPa, the elongation is 31%–35%, and the transverse Charpy V-notch impact energy at 0℃ is 85–112 J. It can withstand 95% of the specified minimum yield strength in solution A for 720 hours according to NACE™ 0177 A method without cracking or fracture. It also shows no cracking after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

3. A 60ksi grade sulfur-resistant oil casing, characterized in that, The 60ksi grade anti-sulfur oil casing comprises the following chemical components by mass percentage: C 0.10%~0.13%, Si 0.25%~0.37%, Mn 1.15%~1.28%, P 0.008%~0.012%, S 0.0015~0.0020%, Al 0.010%~0.015%, Ca 0.010%~0.015%, N 0.0035%~0.0042%, O 0.0015%~0.0019%, H 0.00010%~0.00014%, Cr 0.18%~0.25%, V 0.045%~0.060%, RE 0.0010%~0.0035%, balance Fe and unavoidable impurities; The metallographic structure of the 60ksi grade oil casing is acicular ferrite and granular bainite, with a grain size of 10.5–11.

5. The yield strength is 490–535 MPa, the tensile strength is 620–665 MPa, the elongation is 31%–34%, and the transverse Charpy V-notch impact energy at 0℃ is 96–112 J. It can withstand 95% of the specified minimum yield strength in solution A for 720 hours according to NACE™ 0177 A method without cracking or fracture. It also shows no cracking after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

4. A 60ksi grade sulfur-resistant oil casing, characterized in that, The 60ksi grade anti-sulfur oil casing comprises the following chemical components by mass percentage: C 0.10%~0.13%, Si 0.28%~0.37%, Mn 1.18%~1.28%, P 0.009%~0.012%, S 0.002%, Al 0.010%~0.014%, Ca 0.011%~0.015%, N 0.0038%~0.0042%, O 0.0015%~0.0019%, H 0.00010%~0.00014%, Cr 0.18%~0.25%, V 0.048%~0.060%, RE 0.0010%~0.0035%, balance Fe and unavoidable impurities; The metallographic structure of the 60ksi grade oil casing is acicular ferrite and granular bainite, with a grain size of 10.5-11.

5. The yield strength is 510-535 MPa, the tensile strength is 635-665 MPa, the elongation is 31%-33%, and the transverse Charpy V-notch impact energy at 0℃ is 96-112 J. It can withstand 95% of the specified minimum yield strength in solution A for 720 hours according to NACE™ 0177 A method without cracking or fracture. It also shows no cracking after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

5. A 60ksi grade sulfur-resistant oil casing, characterized in that, The 60ksi grade anti-sulfur oil casing comprises the following chemical components by mass percentage: C 0.11%~0.13%, Si 0.28%~0.32%, Mn 1.18%~1.22%, P 0.009%~0.010%, S 0.002%, Al 0.012%~0.014%, Ca 0.011%~0.012%, N 0.0038%~0.0040%, O 0.0015%~0.0019%, H 0.00010%~0.00014%, Cr 0.23%~0.25%, V 0.048%~0.055%, RE 0.0030%~0.0035%, balance Fe and unavoidable impurities; The metallographic structure of the 60ksi grade oil casing is acicular ferrite and granular bainite, with a grain size of 10.5-11.

0. The yield strength is 525-535 MPa, the tensile strength is 650-665 MPa, the elongation is 31%-32%, and the transverse Charpy V-notch impact energy at 0℃ is 96-100 J. It can withstand 95% of the specified minimum yield strength in solution A for 720 hours without cracking or fracture according to NACE™ 0177 A method, and no cracks appear after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

6. A 60ksi grade sulfur-resistant oil casing, characterized in that, The 60ksi grade anti-sulfur oil casing comprises the following chemical components by mass percentage: C 0.12%~0.15%, Si 0.17%~0.25%, Mn 1.05%~1.15%, P 0.008%~0.011%, S 0.0015%~0.0017%, Al 0.015%~0.018%, Ca 0.007%~0.010%, N 0.0035%~0.0045%, O 0.0016%~0.0017%, H 0.00011%~0.00013%, Cr 0.15%~0.20%, V 0.035%~0.045%, RE 0.0025%~0.0050%, with the balance being Fe and unavoidable impurities; the metallographic structure of the 60ksi grade oil casing is acicular ferrite and granular bainite, with a grain size of 10.0~11.0, a yield strength of 470~490MPa, a tensile strength of 595~620MPa, an elongation of 34%~35%, and a transverse Charpy V-notch impact energy of 85~104J at 0℃. It can withstand 95% of the specified minimum yield strength in solution A for 720 hours without cracking or fracture according to NACE™ 0177 A method, and no cracks appear after 96 hours of testing in saturated H2S solution according to NACE™ 0284.

7. A method for preparing a 60ksi grade anti-sulfur oil casing according to any one of claims 1-6, characterized in that, Includes the following steps: Based on the chemical composition of 60ksi grade anti-sulfur oil casing, after batching, smelting, and continuous casting, a continuously cast billet is obtained. The continuously cast bar billet is subjected to hot piercing and hot continuous rolling, then controlled rolling with fixed diameter reduction, followed by controlled cooling and online self-tempering to obtain a tube billet. After hot straightening the tube blank, the 60ksi grade sulfur-resistant oil casing is obtained.

8. The method for preparing 60ksi grade sulfur-resistant oil casing according to claim 7, characterized in that, Before hot piercing the continuously cast billet, a segmented heating step is included, and the process parameters for the segmented heating are as follows: The preheating section temperature is ≤900℃; the heating section temperature is 1100~1200℃; the soaking section temperature is 1230~1280℃, and the soaking section holding time is 150~240min; The temperature used for the thermal piercing is 1150–1220℃, and the piercing ratio is 3.0–4.

0. The process parameters for the hot continuous rolling are as follows: The rolling temperature is 1050~1150℃, and the total rolling deformation is ≥70%.

9. The method for preparing 60ksi grade sulfur-resistant oil casing according to claim 7, characterized in that, The process parameters for fixed diameter reduction and controlled rolling are as follows: The temperature before the diameter reduction is 950-1050℃, the cumulative deformation during diameter reduction is 20%-40%, and the final rolling temperature is 850-950℃. The process parameters for controlling cooling are as follows: The inner and outer surfaces of the tube are cooled simultaneously. The initial cooling temperature is 850–950℃, the final cooling temperature is 450–600℃, and the cooling rate is 10–50℃ / s.

10. The method for preparing 60ksi grade sulfur-resistant oil casing according to claim 7, characterized in that, The process parameters for online self-tempering are as follows: The self-tempering temperature is 500–650℃, and the self-tempering time is 30–120s; The temperature for hot straightening is 450–610℃.